2016
DOI: 10.1007/s11842-016-9351-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Silviculture Appraisal to Characterise Stand and Determine Silviculture Priorities of Community Forests in Nepal

Abstract: Community forestry in Nepal is an example of a successful participatory forest management program. Developments in community forestry in four decades have focused on the social and governance aspects with little focus on the technical management of forests. This paper presents a silviculture description of community forests and provides silviculture recommendations using a rapid silviculture appraisal (RSA) approach. The RSA, which is a participatory technique involving local communities in assessing forests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Though one of the main objectives of forest management mentioned in the FMP is maintaining forest tree diversity, the dominance of economically valuable species is increasing in the study sites. This is confirmed by a study of six CFUGs in the mid-hills of Nepal [44]. The authors conclude that the current harvesting practices pose a threat to species diversity.…”
Section: How Tree Harvesting Decision Affect Tree Quality?mentioning
confidence: 55%
See 1 more Smart Citation
“…Though one of the main objectives of forest management mentioned in the FMP is maintaining forest tree diversity, the dominance of economically valuable species is increasing in the study sites. This is confirmed by a study of six CFUGs in the mid-hills of Nepal [44]. The authors conclude that the current harvesting practices pose a threat to species diversity.…”
Section: How Tree Harvesting Decision Affect Tree Quality?mentioning
confidence: 55%
“…Trees are like straight boles without or very less tapering, which is a sign of stiff competition among species, which may retard their growth in the future. Adoption of "protective forest management based on limited use by the MFSC" has resulted in the promulgation of harvesting prescriptions resembling the one size fits all approach, which was also observed in the study of [44], where the FMP and prescriptions are identical.…”
Section: Tree Harvesting Quantity-what Governs It?mentioning
confidence: 85%
“…DFRS (2015) estimated seedlings (<1.3 m height) of 10,095/ ha, small saplings (≥1.3 m height, < 5 cm DBH) of 1045/ha, large saplings (5-10 cm DBH) of 426 /ha, small poles (10-20 cm DBH) of 287/ ha, large poles (20-30 cm DBBH) 79 /ha, small saw log (30-50 cm DBH) of 46 stems/ha and large saw log (≥ 50 cm DBH) of 18 stems/ha. This forest structure is confirmed by few case studies including Cedamon et al (2016) and Awasthi et al (2015). The current stand structure of community forests in Nepal has been achieved through harvesting based on ad hoc selection and sometimes high grading creating openings on the stand allowing natural regeneration to occur.…”
Section: Taxonomic Description and Distributionmentioning
confidence: 64%
“…A target basal area of 30 m 2 has been widely used in selection system and is adopted by the EnLiFT Project as suitable for community forests in Nepal. It is to be noted however that many community forests have basal areas <30 m 2 (Cedamon et al, 2016), the aim therefore for selection system is basal area increase from high quality trees. The rapid silviculture appraisal conducted by Cedamon et al (2016) revealed that the diameter limits for residual trees on community forests ranges from 40 to 50 cm (though a few trees larger than 50 cm may present and protected as mother trees).…”
Section: Dbq Approach For Single Tree Selection System On Nepal's Commentioning
confidence: 99%
See 1 more Smart Citation